Essays on financial development and economic growth - Hosford, Fraser Walter (Trinity College (Dublin, Ireland). Department of Economics, 2003)
This thesis is a collection of essays on the relationship between financial development and economic growth. The thesis is introduced in Chapter One, which talks about the motivation for the thesis and outlines the structure of the remaining chapters.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin